5G: 2020 and Beyond - Prasad, Ramjee (Taylor & Francis, 2014)
The future society would be ushered in a new communication era with the emergence of 5G. 5G would be significantly different, especially, in terms of architecture and operation in comparison with the previous communication generations (4G, 3G...). This book discusses the various aspects of the architecture, operation, possible challenges, and mechanisms to overcome them. Further, it supports users? interac- tion through communication devices relying on Human Bond Communication and COmmunication-NAvigation- SENsing- SErvices (CONASENSE).Topics broadly covered in this book are; • Wireless Innovative System for Dynamically Operating Mega Communications (WISDOM)• Millimeter Waves and Spectrum Management• Cyber Security• Device to Device Communication